2017
DOI: 10.1039/c7nj01714f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal engineering of a series of complexes and coordination polymers based on pyrazole-carboxylic acid ligands

Abstract: Three new complexes and two coordination polymers have been synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Bipyrazolic ester compounds 1-7 were first synthesized and then converted to their corresponding acid derivatives L1-L7 using a simple hydrolysis reaction in alkaline medium as reported in our previous works [22][23][25][26][27][28]. The structure of these intermediate compounds was checked by spectroscopic and spectrometric methods.…”
Section: Synthesis Of C1-c7mentioning
confidence: 99%
See 1 more Smart Citation
“…Bipyrazolic ester compounds 1-7 were first synthesized and then converted to their corresponding acid derivatives L1-L7 using a simple hydrolysis reaction in alkaline medium as reported in our previous works [22][23][25][26][27][28]. The structure of these intermediate compounds was checked by spectroscopic and spectrometric methods.…”
Section: Synthesis Of C1-c7mentioning
confidence: 99%
“…Furthermore, bipyrazolic compounds functionalized with two carboxylic groups (Fig. 1) have attracted more attention due to their complexing properties toward metal cations [21][22][23]. In 2008, Chandrasekhar et al reported the synthesis and structure of the first dinuclear triorganotin (IV) [(Ph3Sn)2 (µ-LH) (H2O)] based on bi(pyrazole), obtained from the reaction of (Ph3Sn)2O with 3,5-pyrazoledicarboxylic acid (LH) [24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have reported the crystal structures of Co(II)/Cu(II) coordinated complexes of pyrazole-dicarboxylate acid ligand and established their supramolecular structures [16]. In another work, we have demonstrated the effect of the aliphatic backbone of the bis-pyrazole-bis-carboxylate ligand on the supramolecular structures of their Co(II)/Cu(II)/Cd(II) coordination complexes [17]. In a further account, we have studied the effect of anions and hydrogen bonding on the supramolecular structural diversities of Cu(II) and Mn(II) coordination complexes obtained from a novel bis-pyrazole ligand [18].…”
Section: Introductionmentioning
confidence: 94%
“…Carboxy-substituted pyrazoles were used for the construction of highly porous metal-organic frameworks [ 18 , 19 , 20 , 21 ]. Carboxylic acids based on bis(pyrazol-1-yl)alkanes are much less explored and only a few research papers were published so far [ 22 , 23 , 24 , 25 ]. In addition, a series of works devoted to the synthesis of metal-organic frameworks based on structurally related bis(4-carboxyphenylpyrazol-1-yl)methane was carried out by Sumby et al, the presence of the free chelating units in the structure of the framework allowed them to prepare catalysts with single metal sites [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%